1979
DOI: 10.3109/00498257909042344
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidative Metabolism of 1-Bromopropane in the Rat

Abstract: 1. The metabolism of 1-bromopropane in the rat has been re-investigated. The previously known metabolites have been isolated and confirmed as the three mercapturic acids N-acetyl-S-propyl cysteine, N-acetyl-S-propyl cysteine-S-oxide and N-acetyl-S-(2-hydroxypropyl)cysteine. 2. Three further metabolites have been isolated from the urine of rats treated with 4-bromopropane. These have been identified as 3-bromopropionic acid and the mercapturic acids N-acetyl-S-(3-hydroxypropyl)cysteine and N-acetyl-S-(2-carboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…The presence of propylene oxide is supported by urinary N-acetyl-S-(2-hydroxypropyl)cysteine (Barnsley et al 1966;Jones and Walsh 1979) and glycidol (Ishidao et al 2002) in rats exposed to 1-bromopropane, and production of 1,2-propanediol and 2-hyroxypropylglutathione in microsomal and/or glutathione-added incubation (Tachizawa et al 1982). While it is not clear whether metabolic activation plays a role in the toxicities of these compounds, the understanding of such a process might allow us to identify the reason for the difference in toxicities of the two bromopropanes.…”
Section: Human Cases Of 1-bromopropane Toxicitymentioning
confidence: 98%
“…The presence of propylene oxide is supported by urinary N-acetyl-S-(2-hydroxypropyl)cysteine (Barnsley et al 1966;Jones and Walsh 1979) and glycidol (Ishidao et al 2002) in rats exposed to 1-bromopropane, and production of 1,2-propanediol and 2-hyroxypropylglutathione in microsomal and/or glutathione-added incubation (Tachizawa et al 1982). While it is not clear whether metabolic activation plays a role in the toxicities of these compounds, the understanding of such a process might allow us to identify the reason for the difference in toxicities of the two bromopropanes.…”
Section: Human Cases Of 1-bromopropane Toxicitymentioning
confidence: 98%
“…Bromide ions are not further metabolized but are eliminated mainly through the kidneys (Ryan and Baumann 1999). Urinary Br (-) elevated substantially above normal (reference value = 10 mg/l) represents accumulated exposure over the previous week or two, as Br (-) is excreted slowly (Jones and Walsh 1979). Hanley et al (2006) demonstrated that urinary Br (-) is an effective biomarker of 1-BP for highly exposed foam cushion workers exposed to spray adhesives [Geometric mean (GM) = 92 ppm for sprayers; GM = 11 ppm for other jobs].…”
Section: Introductionmentioning
confidence: 99%
“…A brief summary showing the proposed and generally accepted metabolic pathways of 1-BP is shown in Fig. 1, including the formation of 3-bromopropionic acid (3-BPA) metabolite [12], which is the focus of this study. The mercapturic acids, as well as 3-BPA, have been detected in urine from the rat [12].…”
Section: Introductionmentioning
confidence: 99%
“…1, including the formation of 3-bromopropionic acid (3-BPA) metabolite [12], which is the focus of this study. The mercapturic acids, as well as 3-BPA, have been detected in urine from the rat [12]. The metabolic profile has not been studied well for the human.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation